2022
DOI: 10.3390/ijerph19063174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Δ9-Tetrahydrocannibinol (THC) on Obesity at Different Stages of Life: A Literature Review

Abstract: The Cannabis sativa plant has historically been used for both recreational and medical purposes. With the recent surge in recreational use of cannabis among adolescents and adults in particular, there is an increased obligation to determine the short- and long-term effects that consuming this plant may have on several aspects of the human psyche and body. The goal of this article was to examine the negative effects of obesity, and how the use of Δ9-tetrahydrocannibinol (THC) or cannabidiol (CBD) can impact rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 204 publications
(344 reference statements)
0
10
0
Order By: Relevance
“…However, other studies that investigated the impact of CBD or THC on food intake showed contradictory results. It has been reported that THC increases appetite and subsequent food intake [20]. Studies show that the hyperphagic effects of THC are mostly acute and are absent after a few days of administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies that investigated the impact of CBD or THC on food intake showed contradictory results. It has been reported that THC increases appetite and subsequent food intake [20]. Studies show that the hyperphagic effects of THC are mostly acute and are absent after a few days of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence implies that PCE is associated with long-term energy homeostasis and metabolic effects (40,47), although the evidence surrounding this area, and the directional nature of these effects, is equivocal. The overarching aim of this study was to use a cannabis vapor model to investigate if PCE is associated with increased risk for developing obesity, diabetes and/or abnormal eating habits in adulthood, with additional focus on diet and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies imply that PCE is associated with higher BMI and fat mass during childhood (14, 15, 39) and this abnormal ‘catch-up growth’ is hypothesized to increase the risk for developing obesity later in life (47). In our chow-fed rats, PCE had no effect on bodyweight or weight gain during late adolescence (P50) and early adulthood (P77), as well as no effect on plasma leptin (indirect measurement of adiposity).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cannabis use on metabolic health and obesity risks are speculated to be dependent on several factors including differing patterns of cannabis use, specifically with regards to THC dose, the duration and daily frequency of use, and the length of use (i.e., acute vs chronic) [34]. This highlights the necessity for conducting more appropriately designed, controlled, and highly powered pre-clinical and clinical studies assessing the effects of cannabis use regimens on energy balance in the short and long-term, as well as its potential for alleviating cachexia in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…These cannabis feeding effects have therapeutic potential to stimulate weight gain in patients experiencing wasting associated with anorexia nervosa, chemotherapy, and HIV [32, 33]. Alternatively, in healthy individuals, cannabis driven feeding could be maladaptive, disrupting homeostatic feeding patterns and energy balance [34]. Therefore, further research is essential to assess how cannabis alters feeding behaviours, energy balance and body weight.…”
Section: Introductionmentioning
confidence: 99%